Technical assessment of the influence of rooftop solar power system on power loss of the ray-shaped urban distribution grid in Vietnam - Dr. Giang; Trần Đông; Nguyen Huu, Assoc.Prof.Dr Duc (Journal of Military Science and Technology, 2024)
The penetration of solar power into the distribution grid in general has fundamentally changed the nature of the load from only power consumption to both consumption and power generation into the grid. Because of that, the flow of current in the grid also changes, there are cases where the curent runs backwards from the load to the transformer. This paper introduces the results of research to assess the influence of rooftop solar power (PV) on the power loss of urban distribution grids in Vietnam. First, the typical structure of the distribution grid is selected to simulate the conditions of penetration and locations of PV on each phase along the length of the line. The solar radiation intensity and the typical load profile of the urban distribution grid are also taken into account to observe changes of power loss in the grid. The research results show that under the influence of PV, the power loss has a great change according to the penetration level and the variation of the load.